2012
DOI: 10.1210/en.2012-1241
|View full text |Cite
|
Sign up to set email alerts
|

The Potassium Channel, Kir3.4 Participates in Angiotensin II-Stimulated Aldosterone Production by a Human Adrenocortical Cell Line

Abstract: Angiotensin II (A-II) regulation of aldosterone secretion is initiated by inducing cell membrane depolarization, thereby increasing intracellular calcium and activating the calcium calmodulin/calmodulin kinase cascade. Mutations in the selectivity filter of the KCNJ5 gene coding for inward rectifying potassium channel (Kir)3.4 has been found in about one third of aldosterone-producing adenomas. These mutations result in loss of selectivity of the inward rectifying current for potassium, which causes membrane d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 27 publications
0
40
0
Order By: Relevance
“…Overexpression of wild-type KCNJ5 in human adrenocortical cells was reported by Oki et al (382) ). Interestingly, however, in nontransfected human adrenal cells, administration of a GIRK inhibitor (tertiapin Q) had no effect on cell membrane current (263) and siRNA targeted KCNJ5 knockdown did not affect aldosterone production (382), suggesting that endogenously expressed KCNJ5 may be relatively inactive in normal ZG.…”
Section: F the "New" Genetics: Somatic And Germline Mutations In Genmentioning
confidence: 94%
“…Overexpression of wild-type KCNJ5 in human adrenocortical cells was reported by Oki et al (382) ). Interestingly, however, in nontransfected human adrenal cells, administration of a GIRK inhibitor (tertiapin Q) had no effect on cell membrane current (263) and siRNA targeted KCNJ5 knockdown did not affect aldosterone production (382), suggesting that endogenously expressed KCNJ5 may be relatively inactive in normal ZG.…”
Section: F the "New" Genetics: Somatic And Germline Mutations In Genmentioning
confidence: 94%
“…Gomez-Sanchez (University of Mississippi Medical Center, Jackson, Mississippi, USA) (48). pLX303 KCNJ5 WT was generated from plx303 KCNJ5 G151R using a PCR-based strategy (QuikChange, Stratagene)…”
Section: Methodsmentioning
confidence: 99%
“…Functional studies have demonstrated that GIRK4_Thr158Ala-transduced adrenocortical cells presented a loss in K C selectivity and greater influx of Na C into the cytoplasm resulting in the depolarization of the plasma membrane, thereby activating voltage-gated Ca 2C channels, leading to accumulation of intracellular Ca 2C . Increased intracellular Ca 2C activates the calcium signaling pathway resulting in the synthesis of steroidogenic enzymes and increased aldosterone production (Oki et al 2012b). Recent studies have described different germline KCNJ5 mutations in families with FH3.…”
Section: Familial Hyperaldosteronism Type IImentioning
confidence: 99%